Develando lo que dicen sobre raza y etnia las revistas de salud pública de Colombia - Mosquera Becerra, Janeth (Universidad Icesi, 2015)
This article analyzes how in published studies (1994-2011) in the three main public health journals of Colombia are conceptualized, operationalized and interpreted racial and ethnic categories in relation to the black population. It was identified that are limited the number of published articles that address race or ethnicity; in addition, those notions are used interchangeably, and; it is not showed how is conceptualized and collected those social categories. Under the existence of structural racism, including ethno-racial categories in health research could help to identify processes and dynamics that create and recreate health disparities based on race and ethnicity.
Este artículo analiza cómo en investigaciones publicadas (período 1994-2011) en las tres principales revistas de salud pública de Colombia se conceptualiza, nomina e interpreta la categoría étnico-racial en relación a la población afrodescendiente en el país. Se identificó que es limitado el número de artículos publicados que abordan las nociones de raza o etnia; además, estas se usan de manera intercambiable, y no se conceptualiza ni se explícita el por qué ni cómo se recolectan estas categorías. Bajo la existencia de un racismo estructural, la inclusión de la dimensión etno-racial en las investigaciones de salud, contribuiría a identificar procesos y dinámicas que crean y recrean iniquidades etno-raciales en salud.
Keywords: Producción intelectual registrada - Universidad Icesi; Etnias - Colombia; Afrodescendientes - Colombia; Salud pública; public health; Race